2023
DOI: 10.3390/healthcare11050639
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction with Healthcare Services and the Techniques Used for its Assessment: A Systematic Literature Review and a Bibliometric Analysis

Abstract: Patient satisfaction with healthcare provision services and the factors influencing it are be-coming the main focus of many scientific studies. Assuring the quality of the provided services is essential for the fulfillment of patients’ expectations and needs. Thus, this systematic review seeks to find the determinants of patient satisfaction in a global setting. We perform an analysis to evaluate the collected literature and to fulfill the literature gap of bibliometric analysis within this theme. This review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
4

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 107 publications
3
35
0
4
Order By: Relevance
“…Furthermore, our result was similar to a recently published systematic review by Ferreira et al. (2023), in which 42% of patients only were satisfied with medication availability.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, our result was similar to a recently published systematic review by Ferreira et al. (2023), in which 42% of patients only were satisfied with medication availability.…”
Section: Discussionsupporting
confidence: 92%
“…This result justifies patients' favorability to dispense their medications in the MOH hospitals instead of PHC centers in Jordan (USAID and Jordan Ministry of Health, 2018). Furthermore, our result was similar to a recently published systematic review byFerreira et al (2023), in which 42% of patients only were satisfied with medication availability.…”
supporting
confidence: 91%
“…This observation was substantiated by the findings of Ferreira et al ( 2023), who demonstrated that patient-centred care has the potential to substantially enhance both patient satisfaction and treatment plan adherence. 20…”
Section: Safety Profile and Patient Satisfactionmentioning
confidence: 99%
“…The healthcare system in a developing country like India is continually changing and improving to fulfil the needs of customers (patients), and nowadays, patients are becoming more health-conscious (Singh et al, 2022;Ferreira et al, 2023). To develop strategies to improve customer satisfaction and generate revenue, health service providers are interested in studying customer attitudes and buying decisions (Suhartanto et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The healthcare system in a developing country like India is continually changing and improving to fulfil the needs of customers (patients), and nowadays, patients are becoming more health-conscious (Singh et al. , 2022; Ferreira et al. , 2023).…”
Section: Introductionmentioning
confidence: 99%